Analisis Kualitas Sistem Informasi Administrasi Persuratan Elektronik Pada Aplikasi E-Buddy di Kecamatan Candi Kabupaten Sidoarjo - Niken Ade Herlina; Yuni Lestari (Jurnal Cahaya Edukasi, 2026)
Advances in information technology have encouraged government agencies to implement electronic-based administrative systems to improve the efficiency and quality of governance. The Sidoarjo Regency Government has developed the e-buddy application as one of the implementations of the e-government concept and electronic-based administrative systems. This study aims to analyze the quality of the information system in e-buddy in the electronic correspondence administration process using the Delone & Mclean (2003) information system success model, which consists of six indicators: system quality, information quality, service quality, system usage, user satisfaction, and net benefits. The method used in this study is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Data analysis techniques are carried out in three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the quality of information has been technically met but its utilization is not optimal, so a dropdown feature and increased user literacy are needed. The system quality is not optimal from a technical and non-technical aspect, so a double-check feature, internal cloud storage, and Standard Operating Procedures are needed. The service quality is not optimal from an HR aspect, so technical guidance is needed regularly and providing visual guidance. User user experience is good in Candi District, but it has not been optimally used by all agencies in Sidoarjo Regency, so leadership intervention is needed. User benefits and net benefits are quite good but not optimal, which are influenced by system quality, so regular maintenance and monitoring by the IT team are needed. Overall, the e-buddy application has supported the digitalization of correspondence administration in Candi District, but still requires improvement and development to be more optimal.